Exogenous Abscisic Acid Mediates Berry Quality Improvement by Altered Endogenous Plant Hormones Level in “Ruiduhongyu” Grapevine - Li, Jiajia; Liu, Boyang; Li, Xiangyi; Li, Dongmei; Han, Jiayu; Zhang, Ying; Ma, Chao; Xu, Wenping; Wang, Lei; Jiu, Songtao; Zhang, Caixi; Wang, Shiping (Frontiers in Plant Science, 2021)
Abscisic acid (ABA) plays a key role in fruit development and ripening in non-climacteric fruit. A variety of metabolites such as sugars, anthocyanins, fatty acids, and several antioxidants, which are regulated by various phytohormones, are important components of fruit quality in grape. Here, grape cultivar “Ruiduhongyu” was used to investigate the relationship between endogenous phytohormones and metabolites associated to grape berry quality under exogenous ABA treatment. 500 mg/L ABA significantly improved the appearance parameters and the content of many metabolites including sugar, anthocyanin, and other compounds. Exogenous ABA also increased the contents of ABA, auxin (IAA), and cytokinins (CTKs), and transcription level of ABA biosynthesis and signaling related genes in fruit. Furthermore, a series of genes involved in biosynthesis and the metabolite pathway of sugars, anthocyanins, and fatty acids were shown to be significantly up-regulated under 500 mg/L ABA treatment. In addition, Pearson correlation analysis demonstrated that there existed relatively strong cooperativities in the ABA/kinetin (KT)-appearance parameters, ABA/IAA/KT-sugars, ABA/indolepopionic acid (IPA)/zeatin riboside (ZR)-anthocyanins, and gibberellin 3 (GA3)/methyl jasmonate (MeJA)-fatty acids, indicating that 13 kinds of endogenous phytohormones induced by ABA had different contributions to the accumulation of quality-related metabolites, while all of them were involved in regulating the overall improvement of grape fruit quality. These results laid a primary foundation for better understanding that exogenous ABA improves fruit quality by mediating the endogenous phytohormones level in grape.